Sleep disturbance and recovery during rehabilitation after traumatic brain injury: a systematic review. Issue 8 (9th April 2020) - Lowe, Alex; Neligan, Aidan; Greenwood, Richard
Abstract: Purpose: Sleep disturbance is well recognized following traumatic brain injury, but less is known about the potential effects of this on patients and their recovery. We review the recent literature that investigates the relationship between sleep disturbance in adult patients following a traumatic brain injury and their functioning, disability, and health. Materials and methods: The PRISMA statement was used as a guide to report the systematic review. Embase, PubMed, and the Cochrane library were searched for all research articles published (or in press) in the 10 y prior to 25 May 2018 that investigated the relationship between the development (or treatment) of sleep disturbance of adult patients with a history of traumatic brain injury and patient outcomes, according to the domains of the International Classification of Functioning, Disability, and Health Core Sets for persons with sleep disorders. Two authors independently assessed all identified studies by title and abstract and were included following article review and discussion. Study quality was assessed using the evidence-based library and information practice critical appraisal checklist. Results: Our search identified 27 studies with a wide range in patient populations and assessment measures. Results suggested that sleep disturbance in patients with a history of traumatic brain injury may be associated with the resolution of post-traumatic amnesia and specific impairments of cognition, affective disorders, fatigue, and pain. Some studies indicated that sleep disturbance could be related to an impaired functional ability and reduced quality of life. Limitations of the systematic review included strict inclusion and exclusion criteria and reporting of secondary outcome measures. Conclusions: These findings highlight the relationship between sleep disturbance and patient rehabilitation and outcomes, and therefore the importance of assessing sleep in patients following a traumatic brain injury. Further research is required with more focused patient populations that combine both subjective and objective assessments of sleep to help clarify this relationship. Implications for rehabilitation: Sleep disturbance following traumatic brain injury may be related to the resolution of post-traumatic amnesia, cognitive and affective disorders, fatigue, and pain. Those with a history of traumatic brain injury and sleep disturbance may demonstrate a worse functional ability and report a poorer satisfaction with life. It is important for rehabilitation professionals to take sleep disturbance into account in those patients with a history of traumatic brain injury.